(untitled) - Plutschow, Herbert E. (Tokyo, 1983)
Kyoto is one of Japan's largest cities and the ... Nijo Castle - Floor plan map .... the palace itself can only be visited as part of a guided tour operated by the Imperial Household ... was completely renovated in 2014 and boasts numerous examples of historic art and applied arts ...
Keywords: Kyoto (Nhật Bản),Kyoto (Japan); Mô tả và du hành,Description and travel